ANALISIS PEMBELAJARAN MONOPOLI EKONOMI (MONOKOMI) PADA SISWA BOARDING SCHOOL - Meyta Pritandhari Meyta Pritandhari; Triani Ratnawuri (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
The learning process is one measure of educational success. Many factors influence students to do not focus when studying night guidance. The learning strategy that is usually used is the lecture method must be changed to be more interesting for students to learn. One effort to increase student interest in learning is to use the Monopoly Economic learning media (MONOKOMI). This study was conducted on students of class X Boarding School. This research was conducted on class X Islamic Boarding School MAN 1 Metro. This study aims to analyze students' interest in the use of Monokomi. This study uses collection methods, namely interviews, questionnaires, and documentation. The results of this study state that learning using monochrome learning media gets a percentage value of 90% with the category "very good" which means that learning media is very good for use in learning. Based on these data, there is a 30% increase when using monochrome learning media in increasing students' interest in learning.Keywords: learning media, learning interest, monokomi, monopoly